PECULIARITIES OF LABORATORY DIAGNOSTICS OF INTRAUTERINE INFECTION - Yulayeva I.A.; Yaxshiboyeva D. (JOURNAL OF NEW CENTURY INNOVATIONS, 2024)
In the case of suspected IUI, the most common infections tested for are toxoplasmosis, CMVI, herpes infection, chlamydia and, more recently, infectious mononucleosis. Examination of the mother during pregnancy in most cases makes it possible to exclude those infections for which negative results have been obtained, and to conduct targeted examination of the child. If the mother is not examined, it is recommended to perform a parallel blood test on the mother and the child for a prompt and more reliable diagnosis of IUI. In this case, there may be different situations that cause difficulties for doctors in interpreting the results. It is in the diagnosis of neonatal pathology the greatest diagnostic value have additional tests (detection of low-avidity antibodies, IgA, antigens or DNA pathogen) [1,2,3].